Cash crop or food crop? socioeconomic and geopolitical factors affecting smallholder farmer crop selection in times of crisis in southwestern Tajikistan - Zakirova, Aksana; Alff, Henryk; Schmidt, Matthias (Frontiers in Agronomy, 2023)
Tajikistan's agricultural sector, primarily dominated by cotton cultivation, has experienced significant changes since the Soviet era. Although farmers introduced food crops into agricultural production to ensure food security after the collapse of the Soviet Union in 1991, the government still mandates that cotton cultivation occupy a considerable portion of Tajikistan's limited irrigated land. However, following the recent Covid-19 pandemic crisis, farmers have encountered the need to reassess their agricultural practices, given constrained governmental assistance and a range of socioeconomic considerations. This research adopts resilience as a conceptual framework to examine the coping strategies of smallholder farmers in the Khatlon region of Tajikistan, with a specific emphasis on the period spanning from 2019 to 2022. At the outset, our research employed the snowballing technique to increase respondent participation, later transitioning to a representative sample size that facilitated the collection of qualitative data from around 100 semi-structured interviews, 10 focus groups, and personal visits to agricultural fields over the course of four years. The paper not only demonstrates the overall creativity of Tajikistani farmers in growing and selecting non-cotton crops in this most recent period of crisis, but also points to wealthier farmers’ generally greater willingness to adopt technological innovations and gain new knowledge to apply to them. Although these strategies have been taken in order to address farmers’ immediate needs in troubled times against the backdrop of the existing state cotton policy, their sustainability remains uncertain. While the qualitative focus of this study bears certain inherent limitations, the data collected nevertheless show that this period of crisis has been generative for many farmers as they seek out new methods of subsistence.